Standard Specification for Seamless Carbon Steel Pipe for High-Temperature Service - American Society For Testing And Materials (United States ASTM, 2015)
This specification covers carbon steel pipe for high-temperature service. These pipes are suitable for welding, bending, flanging, and similar forming operations. Mechanical testing of the specimens shall include tensile, bending, flattening, hydrostatic and nondestructive electric tests. Specimens undergoing bending tests shall consist of sections cut from a pipe. For flattening tests, the specimens shall be smooth on the ends and burr-free, except when made on crop ends. All tests shall be performed in room temperature. If any test specimen shows flaws it can be discarded and substituted for another test specimen. Before testing, if a specimen has scribe scratches, a retest shall be allowed. A retest shall also be allowed if a specimen breaks in an inside or outside surface flaw.
Keywords: Pipe, Steel -- Standards; Pipe, Steel -- Specifications; Pipe, Steel -- Welding